Trends of cancellation of notified cosmetic products in Malaysia / Bazilah Mat Daud - Mat Daud, Bazilah (2014)
Background : Cosmetic products are being used by all people around the world. Though cosmetic products are applied externally to the human body, the safety of the products has never been investigated in clinical trials and they are not required to undergo poison screening for marketing notification. Objective : The aim of this study was to determine the trends of cancellation of cosmetic products in Malaysia with regard to their claim indications and poison contents. Methods : Data for cancelled cosmetic products in Malaysia and their poison contents within 2008 to 2013 were obtained from the official website of National Pharmaceutical Control Bureau (NPCB), Ministry of Health Malaysia. Data for claim indications of the cancelled products was obtained at NPCB Cosmetic Unit at Petaling Jaya. A descriptive statistic was applied to the obtained data. Results : The total cosmetic products cancelled in Malaysia from 2008 to 2013 was 60; six in 2008, 12 in 2009, 12 in 2010, five in 2011, 12 in 2012 and 13 in 2013. Skin whitening (16/60), moisturizer (9/60) and UV protector (9/60) were the most commonly cancelled products. Tretinoin (26/67) was the most common poison found in the cancelled products, followed by hydroquinone ( 19/67) and heavy metals (17/67).